VUCA Era: The Role of Business and Knowledge Management System to Build Coastal Community Economic Resilience - Pujianto, wahyu Eko; Novie, Muhafidhah; Larassaty, Ayu Lucy; Burhanudin, Muhammad (JURNAL AKUNTANSI DAN MANAJEMEN, 2023)
The challenge for society in the digital era is the emergence of Volatility, Uncertainty, Complexity, and Ambiguity, or VUCA, so sensitivity, adaptivity, and constructive understanding are needed for all elements in a country, especially society. This study aims to describe how efforts to build coastal community resilience in the VUCA era through the business sector and knowledge management. This research is qualitative with a grounded theory method with a Straussian approach. Research data were collected through indirect observation and interviews so that they could be analyzed through detailed narratives. Based on the research results, it is known that coastal communities can face the VUCA era through the development of the business sector, especially on a small and medium scale. Even so, efforts are needed to implement a knowledge management system so that every business actor in the coastal area can innovate and compete in the VUCA era. The existence of business activities accompanied by systematic knowledge management will improve coastal communities economic conditions sustainably, even in the VUCA era.